(3GdCSWbSGJ Ydi QCi HbQGWs - (3LGdjfhSs
(3ChdgG (B:s
(3hGMO ef Pdc Efc Ef BKQJ Cf JCNPRfLGQG hJhJjG hRfLaQG aJSMbgG LejYkG SMbkG fGYekG MJi JUjQ cGdZHGQ XffJ CfgG cdgG TF s
(3BNQgG (B:s
(3aHTOI GdLPH jJHYg hGMO ef SGFQ GdCNdGW , hgh GdPi jJdh ai WHjYI Pdc GdNdW GdPi jLJPH bSQkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdSWhQ GdChdi eWehSIs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B22 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdhWfjI HeOQjO (B(1/5011) s
Keywords: (3GdWHs